Prosedur Teknis Biopsi Paru Menggunakan Panduan CT Scan Thorax - Andi Nur Intan Wulandari; Zulkifli Tri Darmawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2026)
This study explores the technical aspects of CT-scan–guided thoracic biopsy performed on lung tumor cases at the Radiology Department of Ibnu Sina YW-UMI Hospital, Makassar. Using a qualitative case-study approach, the research focuses on a radiographer who was directly involved in the procedure. Observations covered the entire workflow of the examination, beginning with patient preparation, positioning within the gantry, placement of external markers to identify the biopsy target, selection of technical parameters, and the execution of the biopsy under CT guidance. Each stage was reviewed to assess how closely the routine practices aligned with established standards for CT-guided biopsy. The findings show that most technical steps followed the recommended guidelines, including patient positioning, scanning technique, slice thickness selection, sterilization procedures, and the insertion of a spinal needle. A notable finding of this study is the use of lead-based markers, which produced clearer visualization compared to commonly used catheter-residual markers, thereby improving the accuracy of target localization. The study further highlights that technical precision plays a crucial role in obtaining adequate tissue samples while reducing the likelihood of complications such as pneumothorax. Overall, this research provides an empirical overview of how CT-guided thoracic biopsy is carried out in practice..